Основы государства и права: пособие для поступающих в юридические вузы / Л. А. Морозова - Морозова Людмила Александровна (Institutiones, 2000)
Экземпляры: аб. (2002) / Инвентарный номер: 44157 / Цена: / Сис.шифр: 67.4 / Авт.знак: М 80 / ГРНТИ: 10.07 / ББК: 67.4я73